2021
DOI: 10.15678/eber.2021.090206
|View full text |Cite
|
Sign up to set email alerts
|

Internationalisation motives and the multinationality-performance relationship: The case of Polish firms

Abstract: The objective of the article is to investigate the moderating role of internationalisation motives on the multinationality-performance relationship of Polish firms. Research Design & Methods: Our article uses panel regression models on a dataset of 97 Polish listed "new" MNEs with foreign activities established in the period of 2006-2013, gathered in a primary study. Findings: We found that Polish firms show an inverted U-curve relationship between multinationality and performance, which is contrary to the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…According to the authors, the probability of starting business activity, establishing a business increases with age but only up to a certain moment, and then it decreases. Therefore, the occurring relationship is of inversed U-shape (Barłożewski & Trąpczyński, 2021). The second relationship concerns the age and selfemployment, the authors prove that this form of entrepreneurship grows with age as a result of the accumulation of entrepreneurial resources: knowledge, experience and finance.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 89%
See 1 more Smart Citation
“…According to the authors, the probability of starting business activity, establishing a business increases with age but only up to a certain moment, and then it decreases. Therefore, the occurring relationship is of inversed U-shape (Barłożewski & Trąpczyński, 2021). The second relationship concerns the age and selfemployment, the authors prove that this form of entrepreneurship grows with age as a result of the accumulation of entrepreneurial resources: knowledge, experience and finance.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 89%
“…Therefore, it is less obvious to understand the impact of entrepreneurial competence on the effectiveness of entrepreneurial activities, e.g., internationalization. After all, entrepreneurial success varies, and internationalization itself is often a coincidence of many factors (Barłożewski & Trąpczyński, 2021). It raises the question of the role of entrepreneurial competence against this background.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…In addition to factors as related to these determinants of the internationalisation process, inducing factors should also be considered such as “firm-specific advantages and country-specific factors, e.g. firm size, industry, firm age, experience gathered in foreign market, RandD investments, and institutions in the country of origin” (Barłożewski and Trąpczyński, 2021, p. 86). Studies such as the ones by Kalinic and Brouthers (2021), Haddoud et al .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Existing literature reviews in the field of management have recurred to different methodologies, contingent on the objectives and topics of the literature review. In fact, the aim of this present review is not to devise an exhaustive quantitative overview of existing research on export performance, as such reviews can already be found (Chen et al, 2016;Francioni et al, 2016;Barłożewski & Trąpczyński, 2021;Trąpczyński & Halaszovich, 2021). Instead, the aim of the paper is to develop an overarching conceptual framework for studying export performance, based on the current shortcomings of this research and the proposals how to address them.…”
Section: Literature Review Designmentioning
confidence: 99%